Food Allergy and Helicobacter pylori Infection: A Systematic Review - Ma, Zheng Feei; Majid, Noorizan A.; Yamaoka, Yoshio; Lee, Yeong Yeh (Frontiers in Microbiology, 2016)
Introduction: Based on the hygiene hypothesis, a low prevalence of Helicobacter pylori (H. pylori) infection may explain the recent high prevalence of allergic diseases including food allergy. However, there are very few studies that investigate the relationship between H. pylori and food allergy. Summary: We searched for PubMed, Ovid Medline and the Cochrane library for relevant articles published in English from inception to November 2015. The inverse relationship between H. pylori and food allergy remains unproven because of contradictory and limited evidence at the moment. Likewise, only limited studies have examined the relationship between CagA; one of H. pylori virulence factor and food allergy. On the other hand, in vitro evidence seems to point out a role of H. pylori in the causation of food allergy. The inconsistent results from epidemiological data may be due to small sample size, heterogeneous populations and unstandardised methods or food allergens. Conclusions: Available studies do not support the role of H. pylori in food allergy.